Subsidizing Water Connections in Cameroon : How to Apply Output-Based Aid to an Affermage - Marin, Philippe; Loening, Esther; Drozdz, Jan (World Bank, Washington, DC, 2012)
The Cameroon water connection scheme that started in 2008 is the first GPOBA project to be implemented under an affermage contract. It is also the first subsidized water connection program in West Africa to be implemented through an output-based aid (OBA) mechanism. This note highlights the emerging lessons learned from the design of the project, summarizing the challenges and opportunities in applying OBA to the affermage model and how they were dealt with. A second note will share lessons from the project's implementation.